Genetic and molecular evidence for complement dysregulation in patients with HELLP syndrome. Issue 196 (December 2020) - Bazzan, Mario; Todros, Tullia; Tedeschi, Silvana; Ardissino, Gianluigi; Cardaropoli, Simona; Stella, Stefania; Montaruli, Barbara; Marchese, Cristiana; Roccatello, Dario; Cugno, Massimo
Abstract: Background: HELLP (Hemolysis, elevated liver enzymes and low platelets) syndrome is a severe and acute pregnancy-related disorder that occurs in approximately 2.5 per 1000 deliveries and represents a major cause of maternal and perinatal morbidity and mortality. This syndrome has been suggested to be a microangiopathy and delivery is the only effective treatment. Objectives: The aim of this study was to investigate the pathophysiology of HELLP syndrome by simultaneously exploring complement, haemostasis, autoimmunity and inflammation in relation to the clinical outcome. Methods: We investigated 19 HELLP patients at the time of diagnosis and 3 months after delivery, for complement function, haemostasis and inflammation with immunoenzymatic methods. Complement-related gene variants were also analyzed by next generation sequencing and multiplex ligation-dependent probe amplification. Nineteen age-matched healthy pregnant women served as controls. Results: At diagnosis, HELLP patients, compared to controls, showed significantly higher plasma levels of SC5b-9 (median 710 ng/ml [range 216–1499] vs 253 ng/ml [19–371], P < 0.0001) and of C5a (20.8 ng/ml [5.6–27.5] vs 12.7 ng/ml [3.2–24.6]; P = 0.004), which decreased three months after delivery (SC5b9: 190 ng/ml [83–446] vs 160 ng/ml [107–219]; C5a: 9.28 ng/ml [2.3–21.6] vs 10.7 ng/ml [2.5–21.2]). A significantly higher frequency of genetic variants involving complement regulatory genes was also observed (52.6% vs 15.8%; P = 0.016). Moreover, at HELLP diagnosis, patients showed increased coagulation markers (fragment F1 + 2 and D-dimer; P = 0.0001) while both patients and controls had high thrombin-generation potential that decreased after delivery. Conclusions: In the pathophysiology of HELLP syndrome, complement dysregulation, in addition to coagulation activation, is involved and may represent a potential target for treatment with the aim of delaying delivery. Highlights: HELLP is a major cause of maternal and perinatal morbidity and mortality. To date the only effective treatment for HELLP syndrome is delivery. Complement dysregulation is involved in HELLP pathophysiology. Complement may be a potential target for treatment aimed at delaying delivery.